SPEAKING PROBLEMS IN DOING ORAL PRESENTATION AT ENGLISH AS A FOREIGN LANGUAGE TEACHER EDUCATION PROGRAM OF UNIVERSITAS JAMBI - Ratih Aulia Sari; Rd. M. Ali; Robi Soma (JAMBI-ENGLISH LANGUAGE TEACHING, 2023)
The research was aimed at observing the speaking problems in doing oral presentation in English as a Foreign Language Teacher Education Program at Universitas Jambi. Telephone semi-structured interview was applied in this research to gain the data from nine students of batch 2018 from three classes. The results of this research revealed seven speaking problems found that the students faced in doing an oral presentation. Vocabulary was the most problem the students met, and speaking in gargling was the least problem. The five other issues were getting nervous, pronunciation, grammar, not understanding the material, and not being well-prepared. The students did several things to overcome difficulties: improvisation, asking for help from friends, using Indonesian, and getting the notes. They did various things to overcome those problems depending on the situation while doing an oral presentation. Keywords: speaking problems, oral presentation, English as a Foreign Language Teacher Education Program.